Family functioning and quality of parent-adolescent relationship: cross-sectional associations with adolescent weight-related behaviors and weight status. Issue 1 (December 2016) - Haines, Jess; Rifas-Shiman, Sheryl; Horton, Nicholas; Kleinman, Ken; Bauer, Katherine; Davison, Kirsten; Walton, Kathryn; Austin, S.; Field, Alison; Gillman, Matthew
Abstract Background Little is known about how factors within the general family environment are associated with weight and related behaviors among adolescents/young adults. Methods We studied 3768 females and 2614 males, 14–24 years old in 2011, participating in the Growing Up Today Study 2. We used generalized mixed models to examine cross-sectional associations of family functioning and quality of mother- and father-adolescent relationship with adolescent/young adult weight status, disordered eating, intake of fast food and sugar-sweetened beverages, screen time, physical activity, and sleep duration. In all models, we included participant's age and family structure. Results Eighty percent of participants reported high family functioning and 60 % and 50 % of participants reported high-quality mother and father relationship, respectively. Among both males and females, high family functioning was associated with lower odds of disordered eating (adjusted odds ratio [AOR] females = 0.53; 95 % Confidence Interval [CI] = 0.45–0.63; AOR males = 0.48; CI = 0.39–0.60), insufficient physical activity, i.e., less than 1 h/day, (AOR females = 0.74; CI = 0.61–0.89; AOR males = 0.73; CI = 0.58–0.92), and insufficient sleep, i.e., less than 7 h/day, (AOR females = 0.56; CI = 0.45–0.68; AOR males = 0.65; CI 0.5–0.85). High family functioning was also associated with lower odds of being overweight/obese (AOR = 0.73; CI = 0.60–0.88) and eating fast food one or more times/week (AOR = 0.74; CI = 0.61–0.89) among females only. Among females, high-quality mother and father relationship were both associated with lower odds of being overweight/obese and disordered eating, eating fast food, and insufficient sleep and the magnitude of associations were similar for mother and father relationship quality (AOR range 0.61–0.84). Among males, high-quality mother and father relationship were both associated with lower odds of disordered eating, insufficient physical activity and insufficient sleep, but only father relationship quality was associated with lower odds of overweight/obesity. Conclusions Adolescents/young adults reporting high family functioning and more positive relationships with their parents reported better weight-related behaviors. For weight status, females appear to be affected equally by the quality of their relationship with both parents, whereas males may be more affected by their relationship with fathers.